Enhanced strength and thermal oxidation resistance of shaddock peel-polycarbosilane-derived C–SiC–SiO2 composites - Li, Guo-Qing; Yu, Min; Lin, Guo-Wei; Wang, Yun-Long; Yang, Li-Xia; Liu, Ji-Xuan; Gucci, Francesco; Zhang, Guo-Jun (Elsevier, 2022)
Biomorphic ceramic materials have potential high-temperature applications, owing to their low density, good corrosion resistance and excellent shape capability, but achieving both high specific strength and excellent thermal oxidation resistance is challenging. In this report, shaddock peel-derived C–SiC–SiO2 composites were successfully prepared by the polymer precursor infiltration (PPI) technique with an optimized heating program. The composites prepared at 1600 °C exhibit the highest compressive strength (∼14.0 MPa) and specific strength (∼1.5 × 107 N m/kg), while those sintered at 1200 °C exhibit the highest bending strength (∼27.4 MPa). The composites exhibit good thermal oxidation resistance (up to 1400 °C) with a low weight loss ratio (<0.11 g/cm3), moreover, the compressive strength of the composites sintered at 1200 °C after thermal oxidation at 1400 °C surprisingly increased from 11.6 ± 2.7 MPa to 21.5 ± 3.5 MPa. The PPI technique provides a viable route to introduce Si source into natural materials and the shaddock peel-derived C–SiC–SiO2 composites are light materials with high strength and excellent high-temperature thermal oxidation resistance.
Keywords: Shaddock peel; Polycarbosilane; Composites; Strength; High-temperature oxidation resistance